Plasma concentrations of 25-hydroxyvitamin D in meat eaters, fish eaters, vegetarians and vegans: results from the EPIC-Oxford survey - Crowe, F; Steur, M; Allen, N; Appleby, P; Travis, R; Key, T (Cambridge University Press, 2011)
Objective: Vegetarians and vegans exclude certain food sources of vitamin D from their diet, but it is not clear to what extent this affects plasma concentrations of 25-hydroxyvitamin D (25(OH)D). The objective was to investigate differences in vitamin D intake and plasma concentrations of 25(OH)D among meat eaters, fish eaters, vegetarians and vegans. Design: A cross-sectional analysis. Setting: United Kingdom. Subjects: Plasma 25(OH)D concentrations were measured in 2107 white men and women (1388 meat eaters, 210 fish eaters, 420 vegetarians and eighty-nine vegans) aged 20-76 years from the European Prospective Investigation into Cancer and Nutrition (EPIC)-Oxford cohort. Results: Plasma 25(OH)D concentrations reflected the degree of animal product exclusion and, hence, dietary intake of vitamin D; meat eaters had the highest mean intake of vitamin D (3.1(95% CI 3.0, 3.2) μg/d) and mean plasma 25(OH)D concentrations (77.0 (95% CI 75.4, 78.8)nmol/l) and vegans the lowest (0.7 (95% CI 0.6, 0.8)μg/d and 55.8 (95% CI 51.0, 61.0)nmol/l, respectively). The magnitude of difference in 25(OH)D concentrations between meat eaters and vegans was smaller (20%) among those participants who had a blood sample collected during the summer months (July-September) compared with the winter months (38%, January-March). The prevalence of low plasma concentrations of 25(OH)D (<25 nmol/l) during the winter and spring ranged from <1% to 8% across the diet groups. Conclusions: Plasma 25(OH)D concentrations were lower in vegetarians and vegans than in meat and fish eaters; diet is an important determinant of plasma 25(OH)D in this British population.